Is ivabradine a wonder drug for atypical POTS?. Issue 4 (20th April 2019) - Cheema, Muhammad Arslan; Zain, Muhammad Abdullah; Ullah, Waqas; Cheema, Khadija
Abstract : Syncope is a sudden loss and gain of consciousness. Traditionally, it is caused by the abnormalities of neurological, cardiac or vasovagal systems. We present a case of a 19-year-old woman presenting with recurrent syncopal episodes with no apparent cause. Examination and investigations were unremarkable for any aetiology except positive tilt tests for postural orthostatic tachycardia syndrome. The purpose of this report is to make physicians aware of the unique presentation of this rare aetiology with recurrent syncopal episodes and the novel management approach.